2019
DOI: 10.1021/acs.jpclett.9b01493
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Combining Advanced Particle Size Analysis Techniques To Characterize Cell-Penetrating Peptide–Ferrocifen Self-Assemblies

Abstract: The design of a simple platform to target the delivery of notably hydrophobic drugs into cancer cells is an ultimate goal. Here, three strategies were combined in the same nanovector, in limiting the use of excipients: cell-penetrating peptides, an amphiphilic prodrug, and self-assembly. Light scattering and cryogenic transmission electron microscopy revealed one size population of objects around 100 nm with a narrow size distribution. However, in-depth analysis of the suspension by nanoparticle tracking analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The study of Guyon et al highlighted the essential and complementary contribution of each characterization methods to reflect the reality of the studied nanostructure. 8 In fact, DLS and transmission electron microscopy (TEM) analysis revealed a 100 nm size population with a narrow size distribution. However, high resolution method (NTA, small-angle X-ray scattering and NMR diffusometry) showed the presence of another population of small objects (<2 nm) which represents more than 99% of the matter.…”
Section: Analytical Methods To Purify and Characterize Functionalized...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Guyon et al highlighted the essential and complementary contribution of each characterization methods to reflect the reality of the studied nanostructure. 8 In fact, DLS and transmission electron microscopy (TEM) analysis revealed a 100 nm size population with a narrow size distribution. However, high resolution method (NTA, small-angle X-ray scattering and NMR diffusometry) showed the presence of another population of small objects (<2 nm) which represents more than 99% of the matter.…”
Section: Analytical Methods To Purify and Characterize Functionalized...mentioning
confidence: 99%
“…It was previously pointed out that complementary and more complex methods should be used to provide reliable information even for the determination of one parameter such as the size of nanoparticles. 8,9 Indeed, this characterization step may be much more difficult after surface functionalization, but the complete understanding of the entire structure is crucial before preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the NMR signal is proportional to the number of 1 H nuclei involved weighted by the relaxation effects (smaller species with longer relaxation times yielding to sharper NMR peaks than larger ones) which favor the visibility of a small object. Guyon et al [55] have shown that PFG-NMR was able to identify the main nanoassembly population that was masked in DLS by small traces of large aggregates. Whereas, small formulation residual components such as micelles which can be masked in DLS by the larger main nanomedicine population could be detected [56,57] using PFG-NMR.…”
Section: Identification Of Species In a Mixturementioning
confidence: 99%
“…Effect of Fetal Bovine Serum on SQAd nanoparticles -Characterizing nanoparticles in media as complex as blood plasma is difficult because of the high concentration of blood components of nanometric size. Dynamic Light Scattering (DLS), which is usually used to estimate the size of squalene-based nanoparticles 31,34,46,47 remains a low-resolution method not adapted to study polydisperse assemblies of nanoparticles 48 within a concentrated complex media. By contrast, Small Angle Neutron Scattering is a powerful method for characterizing the squalenoyl conjugated nanoparticles dispersed in D 2 O 47 and is suitable to study multicomponent systems.…”
Section: Small Angle Neutron Scattering (Sans)mentioning
confidence: 99%